Sociolinguistic competence: its content, structural components, and factors influencing its development - Baxramova, Diyora Sanjar qizi (The Lingua Spectrum, 2026)
This article examines sociolinguistic competence as an essential component of communicative competence and clarifies its content, structural components, and the principal factors influencing its development in foreign language learning. Sociolinguistic competence is interpreted as the learner’s ability to select and use linguistic forms appropriately in accordance with social context, interlocutors’ status and roles, communicative purpose, degree of formality, cultural norms, and accepted patterns of interaction. The study synthesizes major theoretical approaches in sociolinguistics, communicative competence, pragmatics, and foreign language methodology. Particular attention is paid to social-contextual awareness, register and style selection, politeness and speech etiquette, sociocultural knowledge, interpretation of social meanings, and sensitivity to language variation. The article also considers linguistic, sociocultural, educational, interactional, and psychological factors that shape the development of this competence. The findings emphasize the importance of contextualized communication, intercultural comparison, authentic language input, reflective activities, and systematic practice in English language education in diverse real-life communication settings.